Conception of Islam in the Religious Study (The Analysis of W.C Smith’s Thought) - Imamul Wathoni (UIN Sunan Kalijaga Yogyakarta, 2021)
Wilfred Cantwell Smith is one of scholars of religion who tries to compose a concept with vague delineation related to Islam as religion. It is in essence much related to the word piety, in turn related much to Iman as instrument through which human grasps the consciousness and fact of God, manifested in Submission to His will. Smith starts by deconstructing religion both as a term and concept, including Islam as species of religion. What is understood as religion is basically nothing on earth, and yet the phenomena of religiousness is easy to discover, namely as response to the Divinity. Such understanding is referred to personal and individual experience. Smith, therefore, understands Islam as self-entity and distinguishable from other, emphasized on several meanings of Islam, 1. Islam is personal submission (in the form of verbal noun, it is ideal and true sense), 2. Islam which is embodied in community (it is refied sense from sociological lens produced by cumulative tradition), 3. Islam in terms of institutionalism that its adherents refer to, be manifested in al-Qur’an and al-Hadits through which its name and all teaching come into being (since it is the fruit of cumulative tradition which adheres to historical process, it is therefore mundane).